Восстановление граничного режима для двухфазного течения в пласте - Гамзаев, Х.М. (Проблемы управления и информатики, 2012)
Розглянуто обернену задачу, пов’язану з відновленням граничної умови в крайовій постановці для рівнянь двофазної течії в пласті. Побудовано різницевий аналог задачі за допомогою методу «неявний за тиском – явний за насиченістю» і запропоновано обчислювальний алгоритм розв’язання отриманої системи різницевих рівнянь. The inverse problem related to restoration of boundary condition in boundary statement for equations of two-phase flow in oil pool is considered. The difference analog of the problem is constructed using the method «implicit by the pressure – explicit by the saturation» and computational algorithm of solving the obtained system of difference equations is presented.